A live vaccine against Neospora caninum abortions in cattle - Reichel, Michael P. (2015)
Recent publications have calculated the considerable losses inflicted by N. caninum oncattle industries world-wide. Vaccination, at least at this stage, appears to be the only viable intervention strategy that appears feasible. The development of a live vaccine against neosporosis should be pursued, in order that its benefits can be transferred as soon as possible to veterinarians and farmers in order to prevent the reproductive, productive and economic losses caused by N. caninum.